A bioavailable cathepsin S nitrile inhibitor abrogates tumor development. Issue 1 (December 2016) - Wilkinson, Richard; Young, Andrew; Burden, Roberta; Williams, Rich; Scott, Christopher
Abstract Background Cathepsin S has been implicated in a variety of malignancies with genetic ablation studies demonstrating a key role in tumor invasion and neo-angiogenesis. Thus, the application of cathepsin S inhibitors may have clinical utility in the treatment of cancer. In this investigation, we applied a cell-permeable dipeptidyl nitrile inhibitor of cathepsin S, originally developed to target cathepsin S in inflammatory diseases, in both in vitro and in vivo tumor models. Methods Validation of cathepsin S selectivity was carried out by assaying fluorogenic substrate turnover using recombinant cathepsin protease. Complete kinetic analysis was carried out and trueK i values calculated. Abrogation of tumour invasion using murine MC38 and human MCF7 cell lines were carried out in vitro using a transwell migration assay. Effect on endothelial tube formation was evaluated using primary HUVEC cells. The effect of inhibitor in vivo on MC38 and MCF7 tumor progression was evaluated using cells propagated in C57BL/6 and BALB/c mice respectively. Subsequent immunohistochemical staining of proliferation (Ki67) and apoptosis (TUNEL) was carried out on MCF7 tumors. Results We confirmed that this inhibitor was able to selectively target cathepsin S over family members K, V, L and B. The inhibitor also significantly reduced MC38 and MCF7 cell invasion and furthermore, significantly reduced HUVEC endothelial tubule formation in vitro. In vivo analysis revealed that the compound could significantly reduce tumor volume in murine MC38 syngeneic and MCF7 xenograft models. Immunohistochemical analysis of MCF7 tumors revealed cathepsin S inhibitor treatment significantly reduced proliferation and increased apoptosis. Conclusions In summary, these results highlight the characterisation of this nitrile cathepsin S inhibitor using in vitro and in vivo tumor models, presenting a compound which may be used to further dissect the role of cathepsin S in cancer progression and may hold therapeutic potential.